PEMBANGUNAN FLASH CARD BERBASIS AUGMENTED REALITY UNTUK MENUNJANG PEMBELAJARAN PADA ANAK PRA SEKOLAH - Abdullah Azzam; Faisal R. M; Muhammad Ridwan A. P (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
Teaching and learning activities at an early age children is important to note especially about learning media used. In the learning process often children do not focus on what is being taught by the teacher because there is nothing more exciting than being taught by the teacher. In addition the level of boredom child will be increased when the media is not interesting again. Great Media affect the child's motivation to learn. The use of technology in learning media is expected to increase the learn motivation in early childhood. This research will be built a learning media such as flash card that uses augmented reality technology that is expected to increase the learn motivation of early childhood. The results showed that the use of flash media cards augmented reality can improve learning outcomes in children seen from the responses given by children when study. Sistem flash cards augmented reality can be run properly and children can use them independently.